Nanostructured natural-based polyelectrolyte multilayers to agglomerate chitosan particles into scaffolds for tissue engineering - Miranda, Emanuel Sá (2011)
The Layer-by-Layer (LbL) deposition technique is a self-assembly process that allows the coating of material's surface with nanostructured layers of polyelectrolytes, allowing to control several surface properties. This technique presents some advantages when compared with other thin film assembly techniques like having the possibility to coat surfaces with complex geometries in mild conditions or to incorporate active compounds. Tissue engineering involves typically the use of porous biodegradable scaffolds for the temporary support of cells. Such structures can be produced by agglomeration of micro-spheres that needs to be fixed into a three dimensional structure. In this work we suggest the use of LbL to promote such mechanical fixation in free-formed micro-spheres assemblies and simultaneously to control the properties of its surface. For the proof of concept the biological performance of chitosan/alginate multilayers is first investigated in two-dimensional models in which the attachment and proliferation of L929 and ATDC5 cells are studied in function of the number of layers and the nature of the final layer. Scaffolds prepared by agglomeration of chitosan particles using the same multilayered system were processed and characterized; it was found that they could support the attachment and proliferation of ATDC5 cells. This study suggests that LbL can be used as a versatile methodology to prepare scaffolds by particle agglomeration that could be suitable for tissue engineering applications.